2019
DOI: 10.1111/ajt.15397
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of eculizumab for the prevention of antibody-mediated rejection after deceased-donor kidney transplantation in patients with preformed donor-specific antibodies

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. Parameter Summary Cumulative number of plasmapheresis treatments, N = 80 21 patients had ≥1 plasmapheresis treatment Day 0, mean (range) 0.1 (0-1) Week 9, mean (range) 1.0 (0-18) Month 12, mean (range) 2.5 (0-57) Delayed graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 47 publications
(111 reference statements)
0
60
0
1
Order By: Relevance
“…All studies report a safety profile of the drug that is consistent with that reported for eculizumab's approved indications like atypical haemolytic uremic syndrome. Results of these trials suggest a potential role of eculizumab in the prevention and treatment of ABMR in patients with DSA [160,161]. Next to ABMR, eculizumab has been investigated for the prevention of DGF (NCT01919346, NCT02145182).…”
Section: Complement Systemmentioning
confidence: 99%
“…All studies report a safety profile of the drug that is consistent with that reported for eculizumab's approved indications like atypical haemolytic uremic syndrome. Results of these trials suggest a potential role of eculizumab in the prevention and treatment of ABMR in patients with DSA [160,161]. Next to ABMR, eculizumab has been investigated for the prevention of DGF (NCT01919346, NCT02145182).…”
Section: Complement Systemmentioning
confidence: 99%
“…Interestingly, only 12% of patients needed post‐transplant plasmapheresis in the eculizumab group, compared with 76% in controls. These important initial findings were the basis for two recent clinical trials, both reported in 2019, on eculizumab‐based induction to prevent early acute AMR in highly sensitized patients with preformed DSA 4,5 . In the single‐arm study of Glotz et al, 5 80 patients transplanted with C5 blockade during the first 9 weeks were compared with pooled analysis of acute AMR data derived from published data and similar results to the Stegall et al series 4 were found (an 8.8% incidence of acute AMR, that is, lower than the 40% expected rate for standard care (SOC) in such high immunological risk recipients).…”
Section: Discussionmentioning
confidence: 95%
“…Eculizumab is a humanized monoclonal antibody that binds to the human C5 complement protein, resulting in terminal complement blockade. Recently, the safety and efficacy of eculizumab to prevent early acute AMR has been studied prospectively in sensitized deceased‐donor and living‐donor kidney allotransplant recipients, suggesting a potential benefit for eculizumab, which was overall well tolerated 3‐5 . However, little is known about the upfront use of eculizumab to treat early and severe acute AMR in allotransplantation, because most reports to date using eculizumab in that setting (mainly as “rescue therapy”) have also included other treatments to remove circulating donor‐specific alloantibodies (DSA), such as plasmapheresis 6 or immunoadsorption and/or administration of intravenous immunoglobulins (IVIG) 2,6‐11 .…”
Section: Introductionmentioning
confidence: 99%
“…Our primary outcomes were patient survival and all‐ and death‐censored graft survival. Kidney graft survival was defined as a functioning kidney without the need for dialysis and pancreas graft survival as a functioning exocrine pancreas without a permanent (>90 days) need for exogenous insulin . Cox proportional hazard regression was used to compare patient and graft survival between recipients of CACPR and non‐CACPR donors.…”
Section: Methodsmentioning
confidence: 99%